Adsorption of Ca(II), Mg(II), Zn(II), and Cd(II) on Chitosan Membrane Blended with Rice Hull Ash Silica and Polyethylene Glycol - F. Widhi Mahatmanti; Nuryono Nuryono; Narsito Narsito (Universitas Gadjah Mada, 2016)
In this research, chitosan based membrane blended with rice hull ash (RHA) silica and polyethylene glycol (PEG) has been applied as adsorbent of Ca(II), Mg(II), Zn(II) and Cd(II) in an aqueous solution. Membrane was synthesized by blending RHA silica and polyethylene glycol into chitosan. Silica and polyethylene glycol blended into the chitosan to improve the mechanical properties and the membrane porous. The membrane was characterized using Fourier Transform infrared (FTIR) spectroscopy, X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and swelling degree analyzer. Adsorption of metal ions investigated was conducted in a batch system with variation of pH, initial ion concentration and contact time. Thermodynamics and kinetics of adsorption were evaluated based on the adsorption data at initial metal ion concentration and contact time variations, respectively. Results showed that the optimum condition of adsorption was at pH 9.0 for Ca(II), 6.0 for both Mg(II) and Zn(II) and 5.5 for Cd(II), and contact time of 24 h for all ions investigated. Kinetics of all investigated metal ion adsorption followed a kinetic model of pseudo-second-order. Adsorption of Ca(II) and Mg(II) on the membrane fitted to Freundlich model with the affinity of 1.266 and 1.099, respectively; and Zn(II) and Cd(II) fitted to Langmuir one with the capacity of 182 and 106 µmol/g, respectively.